Pembangunan Sistem Informasi Bagian Pelayanan dan Administrasi Desa pada Desa Campurejo - Muh. Thanthowi Lathif; Denny Sagita Rusdianto; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Campurejo Village Hall is a service center for the residents and community of Campurejo Village, Sambil Subdistrict, Ponorogo Regency, East Java. The services provided at Balaidesa are quite diverse, such as: filing correspondence, managing population data, village development, and other community needs. Currently, the service is done manually by entering data in an available form or excel file. So that the service process takes quite a longer time. Then, there are problems in data storage that is not centralized and not stored neatly. So that when village officials need certain data, such as: Population Data Reports, Population Recaps Based on Dusun and other data, it will take quite a long time, because they need to find and calculate or group manually again. To overcome these problems, we need an application. The application is a website-based Village Information System (SIDESA). This application will make it easier for village officials to enter data on the available forms and store the data entered in the database so that it is stored neatly and easily accessible for the future. This application uses several programming languages, namely: Mysql, PHP, CSS, JavaScript, etc. The test results of this application get 100% valid for unit testing, integration, and validation. While getting the results of 1 major issues and 3 minor issues in compatibility testing.